In-line and transverse forces on a cylinder near a boundary in oscillatory flow - Tucker, Gregory James (Department of Civil Engineering, 2016)
It was endeavoured to measure the in-line and transverse forces that act on a cylinder placed near a plane boundary in oscillatory flow. The value of performing such work is that it provides information on the forces that may be exerted by surf ace waves on a pipeline or cable mounted near the sea bed. Investigations were carried out in a laboratory, using a water filled flume. The test cylinder was attached to a plywood surface which was fastened to an hydraulic ram which could oscillate horizontally in a sinusoidal mode. Furthermore, this plywood surface, which acted as the boundary, was in contact with the upper free surface of the water in the flume, with the test cylinder submerged in the water under the plywood surf ace. The situation as it occurs in the field has therefore been inverted for this work, and the test cylinder is oscillated while the water remains stationary. Instead of measuring the lift and drag forces directly, pressure transducers were used to obtain the pressure distribution around the circumference of the test cylinder. An integration of these pressures then yielded the lift and drag forces.